Analysis of Students’ Interest in Learning Mathematics Based on Self-Efficacy - Dina Adinda; Nursupiamin Nursupiamin; Riska Elfira (Universitas Wiralodra, 2026)
Mathematics learning plays an important role in developing students’ logical, critical, analytical, and systematic thinking skills. However, low interest in learning mathematics remains a common challenge that affects students’ engagement and learning outcomes. One psychological factor that may influence students’ learning interest is self-efficacy. This study aimed to explore students’ interest in learning mathematics in relation to their levels of self-efficacy. A qualitative descriptive approach was employed, involving eleventh-grade students at MAN 2 Kota Palu. A self-efficacy questionnaire was administered as a preliminary screening tool to classify students into high and low self-efficacy groups, from which four participants were purposively selected for in-depth qualitative analysis. Data were collected through semi-structured interviews, classroom observations, and documentation of students’ assignments. The findings indicated that students with high self-efficacy demonstrated greater persistence, active participation, and willingness to engage in mathematical problem-solving activities. In contrast, students with low self-efficacy tended to exhibit hesitation, reduced participation, and avoidance of tasks perceived as difficult. These results suggest that students’ interest in learning mathematics is influenced not only by cognitive ability but also by their beliefs in their own capabilities. Therefore, fostering students’ self-efficacy is essential to enhance their engagement and interest in mathematics learning.